Digital era governance IT corporations, the state, and E-government [electronic resource] - Dunleavy, Patrick; Margetts, Helen; Bastow, Simon; Tinkler, Jane (Oxford Oxford University Press, 2006)
This book shows how governments in some countries (the United States, Canada, and the Netherlands) have maintained much more effective policies than others (in the United Kingdom, Japan, and Australia). It shows how public managers need to retain and develop their own IT expertise and to carefully maintain well-contested markets if they are to deliver value for money in their dealings with the very powerful global IT industry. This book describes how a critical aspect of the modern state is managed, or in some cases mismanaged.
Includes bibliographical references (p. 260-273) and index.
Keywords: Information technology -- Government policy; Information technology -- Political aspects; Information society